Evidências pré-clínicas do efeito antimaníaco de um antagonista do receptor da angiotensina - Gomes, Julia Ariana de Souza (2014)
The Bipolar Disorder (BD) is a highly prevalent and chronic psychiatric disorder, associated with functional disability and excessive cost to the health system. The pharmacological therapy of BD displays low efficacy due the complex and poorly understood etiology, which makes it imperative to find new therapeutic targets for this disorder. The renin-angiotensin system (RAS) has been studied concerning neurological diseases, and is currently recognized important role of angiotensin II in anxiety and mood disorders. The deregulation of SRA brain is associated with the formation of reactive oxygen species, activation of proinflammatory pathways, reduced neuroplasticity and mitochondrial dysfunction. It is noteworthy that all these events are related to the pathophysiology of BD. Thus, this study aimed to evaluate the effect of candesartan (CDS) in an animal model of mania induced by d-amphetamine (AMPH). The animals were submitted to two treatment protocols. In prevention protocol, animals received CDS (0.1; 0.3; 1 or 3 mg/kg/day), lithium (47.5 mg/kg/day) or vehicle for 14 days and between the 8th and 14th day received AMPH (2 mg/kg/day ip) or saline. In reversal protocol, was administered AMPH or saline for 14 days and between the 8th and 14th day the animals were treated with CDS, lithium or vehicle. The effect of CDS was evaluated on 14th day by exploratory behavior of animals in the open field test used for pre-clinical study of antimanic drugs. The working memory was also evaluated by Y Maze test. Neurochemical analisis of oxidative stress (TBARS and GSH), was assessed in cerebellar vérmix (CV), prefrontal cortex (PF), hippocampus (HPC) and striatum (ST). For evaluate the levels of BDNF, TNF-α e fosfo-Ser9-GSK-3β,we used CDS 0,3 and CDS 1. BDNF and fosfo-Ser9-GSK-3β was assessed only in HPC and TNF-α in HPC and CV. In both treatment protocols, there was an increase in locomotor activity in the animals that received only AMPH, which was prevented and reversed by CDS, whose results were similar to the control group and the animals that received AMPH and lithium. In the memory test, the CDS prevented and reversed the cognitive impairment caused by AMPH and only the CDS doses of 0.1 in prevention protocol and 0.3 in reversal protocol were not successful. Lithium treatment neither prevented nor reversed the cognitive impairment. The CDS increased GSH levels in HPC and CV in the prevention protocol and in PF, HPC and ST in the reversal protocol. The TBARS levels were reduced by CDS in PF, HPC and CV in the prevention protocol and in PF, HPC and ST in the reversal protocol. However, MDA level was increased by higher dose of CDS in ST in prevention protocol and by the two lower doses of CDS in CV in reversal protocol. In both treatment protocols, AMPH reduced BDNF and lithium and both doses of CDS restored the levels of this neurotrophin. In the prevention protocol, AMPH and both doses of CDS reduced the level of phospho-Ser9-GSK-3β that was significantly increased by lithium. The levels of TNF-α were increased by AMPH and reduced by lithium in HPC and VC. CDS prevented the increase of TNF-α in HPC and prevented and reversed this increase in CV. Our findings showed that CDS, similarly to Li, is effective in reversing and preventing AMPH-induced behavioral and neurochemical alterations, providing a rationale for evaluating CDS as a novel antimanic agent, however new pre-clinical studies are necessary.